(7

**r**+ 10)/**r**(**r**+ 1)(**r**+ 2) = A/**r**+ B/(**r**+ 1) + C/(**r**+ 2) A(**r**+ 1...(**r**+ 1) = 7r + 10**r**= 0 --> 2A = 10 --> A = 5**r**= -1 --> -B = 3 --> B = -3**r**= -2 --> 2C = -4...1 Answe

**r**s · Science & Mathematics · 03/01/2013The answer is

**r**= -.5 I didn't know if you wanted the explanation or not but I...: 2r=-1 Divide 2r by both sides and the answer is**r**=-1/2 or -.52 Answe

**r**s · Science & Mathematics · 14/10/2010Simplify: (square the top and bottom of the fraction, then multiply top by

**R**: 22.4 = 14400R/(**R**+139)^2 Clear fraction: (multiply both ...2 Answe

**r**s · Science & Mathematics · 21/10/2009(1+

**r**/m)^m (1+1/(m/**r**))^m (1+1/(m/**r**))^mr/**r**(1+1/(m/**r**))^**r**(m/**r**) as m -> infin, so does m/**r**(1+1/(m/**r**))^**r**(m/**r**) This is e^**r**Lets evaluate the limit mathematically...3 Answe

**r**s · Science & Mathematics · 03/12/2008**r**is rational, so**r**= a / b for some integers a and b, where b is not zero...b^2 = 1 This implies b = 1 or = -1 Since**r**= a / b, it is the case that**r**= a / 1 = a or**r**= a / -1 = -a...1 Answe

**r**s · Education & Reference · 30/09/2011**R**= 1.1926, -4.1926 Try using MathWay.com Hope this helps!4 Answe

**r**s · Science & Mathematics · 07/04/2013The -

**R**was the original format of the DVD created, and created... had to make the name different somehow, so the went with +**R**. They were originally intended for computers and not...3 Answe

**r**s · Computers & Internet · 24/07/2008∑ _{

**r**=1, n} 1= n ∑ _{**r**=1, n}**r**= (n+1)·n/2 ∑ _{**r**=1, n}**r**²= n·(n+1)·(2n+1)/6 ==>...2n**r**+**r**² -n -**r**) = (n²-n)·∑ _{**r**=1, n} 1 + (2n-1)· ∑ _{**r**=1, n}**r**+ ∑ _{**r**=1, n}**r**² = (n²-n)·n + (2n-1)·(n...1 Answe

**r**s · Science & Mathematics · 26/07/2009**R**=4x^2+8x C=x^2+2x**R**-C= 3x^2+6x (**R**-C)'= 6x+6 (**R**-C)"= 6 Now (**R**-C...2 Answe

**r**s · Science & Mathematics · 13/09/2013|

**r**(t)| = constant implies that 1.**r**(t) either doesn't change with t,**r**'(t)=0 or 2. its...would change also by the triangle inequality. In either case since 1.**r**'(t)=0 or 2.**r**(t) dot**r**'(t) =**r**(t)**r**'(t)cos(90) = 0...1 Answe

**r**s · Science & Mathematics · 17/04/2015